Women alone modern contraceptive use decision making and its correlates, evidence from PMA CS 2021 survey - Solomon Abrha Damtew; Fitsum Tariku Fantaye (BMC, 2024)
Abstract Background Women alone contraceptive decisions making has become one of the top burring public health agenda. Despite Contraceptive method options are available and accessible, contraceptive prevalence rate (CPR) in Ethiopia is not far beyond 41%. Evidences showed that the freedom of women to choose the contraceptive method they desired to use is one of the potential determinants for the sluggish pace of increase in contraceptive usage. In this era of sustainable development, determining the level of women own contraceptive use decision making and identifying its correlates is very critical for the ministries and relevant partners' effort in tracking the achievement of Sustainable Development Goal (SDG) 5.2 by providing actionable evidence through informed decision-making with the aim of improving contraceptive uptake; reducing maternal mortality and improve newborn health. Methods Nationally representative cross-sectional data from Performance Monitoring for Action (PMA) 2021 was used in this study. The sample was restricted among2446 married women who have been using or most recently used modern contraceptive method. Cell sample size adequacy was checked using a chi-square test. Frequency was computed to characterize the study participants. Multilevel binary logistics regression was used to identify factors associated with women own contraceptive use decision making. The findings were presented in a form of frequencies, percentage and as an odds ratio using 95% confidence interval. A p-value of 0.05 was used to declare significance. Results This study revealed that higher than one in two women (59.49%; 95% CI: 57.7-61.38%) decide their contraceptive use by themselves. What is more interesting is that 1 in 16 women (6.06%) reported that they did not participated in their contraceptive use decision-making.-. Women aged 20 to 24 years; (AOR: 2.51 (1.04, 4.45)), women who stayed10 and above years in marriage; (AOR: 1.73 (1.08, 2.77)), whose husband and/or partner age is 41 and above years; (AOR: 2.14 (1.06, 4.31)) and those who obtained contraceptive method they desired; (AOR: 2.49 (1.36, 4.57)) had higher odds of deciding their current and/or recent contraceptive use by their own. On the other hand, women mixed feeling if they became pregnant at the time of the survey; (AOR: 0.6 (0.44, 0.91)), women who started using contraceptive at younger age, 19 to 24; (AOR: 0.6 (0.44, 0.81)), those who use long acting and/or permanent method; (AOR: 0.54 (0.41, 0.71)) and those married at younger age, 10 to 19 years; (AOR: 0.28 (0.09, 0.86)) had lower odds of independently deciding their current and/or most recent contraceptive use. Conclusion 59% of women independently decide their contraceptive use which calls up on further improvement to enable each woman to decide by their own, with directing special focus for the 6.06% of women who reported no say in their contraceptive use decision. Activities targeting on enabling women to use the method they preferred, spacing their pregnancy, encouraging women to discuss with their husband on the time and type of contraceptive method they used, advocating and promoting marriage at least to be at the minimum age as indicate by the law and maintain the marriage duration as much as longer are hoped to improve women alone contraceptive use decision making to the fullest.